Safety and efficacy of thrombolysis in telestroke: A systematic review and meta-analysis. (27th September 2016) - Kepplinger, Jessica; Barlinn, Kristian; Deckert, Stefanie; Scheibe, Madlen; Bodechtel, Ulf; Schmitt, Jochen
Abstract : Objective: The aim of this systematic review and meta-analysis was to evaluate the safety and efficacy of IV thrombolysis (IVT) with tissue plasminogen activator (tPA) delivered through telestroke networks in patients with acute ischemic stroke. Methods: We conducted a systematic review and meta-analysis according to PRISMA guidelines. Literature searches on MEDLINE, Embase, and CENTRAL databases covered prospective randomized controlled and nonrandomized studies comparing telemedicine-guided IVT to IVT administered at stroke centers and were published from the earliest date available until April 1, 2015. Outcomes of interest were symptomatic intracerebral hemorrhage, mortality, and functional independence (modified Rankin Scale scores 0–1) at 3 months. Random-effects meta-analysis was used to compute pooled effect estimates and the I 2 statistic to assess heterogeneity. Results: Of 529 records identified, 7 studies totaling 1, 863 patients fulfilled our eligibility criteria. Among these, thrombolysis was largely restricted to the 3-hour time window. Symptomatic intracerebral hemorrhage rates were similar between patients subjected to telemedicine-guided IVT and those receiving tPA at stroke centers (risk ratio [RR] = 1.01, 95% confidence interval [CI] 0.37–2.80; p = 0.978) with low evidence of heterogeneity ( I 2 = 37%; p = 0.189). There was no difference in mortality (RR = 1.04, 95% CI 0.74–1.48; p = 0.806) or in functional independence (RR = 1.11, 95% CI 0.78–1.57; p = 0.565) at 3 months between telemedicine-guided and stroke center thrombolysis. No heterogeneity was identified ( I 2 = 0%, p = 0.964 and I 2 = 52%, p = 0.123, respectively). Conclusions: Our findings indicate that IV tPA delivery through telestroke networks is safe and effective in the 3-hour time window. Lack of prospective trials, however, emphasizes the need to further substantiate these findings in the 3- to 4.5-hour time window. PROSPERO registration information: URL:http://www.crd.york.ac.uk/PROSPERO . Unique identifier: CRD42015017232.